2017
DOI: 10.1186/s13049-017-0349-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia in trauma victims at first arrival of ambulance personnel: an observational study with assessment of risk factors

Abstract: BackgroundHypothermia is common in trauma victims and is associated with increased mortality, however its causes are little known. The objective of this study was to identify the risk factors associated with hypothermia in prehospital management of trauma victims.MethodsThis was an ancillary analysis of data recorded in the HypoTraum study, a prospective multicenter study conducted by the emergency medical services (EMS) of 8 hospitals in France. Inclusion criteria were: trauma victim, age over 18 years, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 15 publications
2
23
0
1
Order By: Relevance
“…Environmental factors can aggravate the inevitable heat loss and especially entrapped patients in austere environments undergoing prolonged extrication can suffer severe hypothermia [8]. Even though there is some evidence regarding hypothermia mitigation during hospital transport, there is no literature on hypothermia prevention in patients that are still entrapped [9].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors can aggravate the inevitable heat loss and especially entrapped patients in austere environments undergoing prolonged extrication can suffer severe hypothermia [8]. Even though there is some evidence regarding hypothermia mitigation during hospital transport, there is no literature on hypothermia prevention in patients that are still entrapped [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is not always specified whether hypothermia was the primary injury (eg, from cold air or water exposure) or developed secondary to another illness (eg, trauma). Many articles focus exclusively on hypothermia resulting secondary to severe trauma because of the high incidence and poor prognosis of these cases …”
Section: Epidemiology: Estimating Incidence and Mortality Of Accidentmentioning
confidence: 99%
“…Many articles focus exclusively on hypothermia resulting secondary to severe trauma because of the high incidence and poor prognosis of these cases. 56 For these reasons, it is difficult based on existing data to differentiate cases of hypothermia that are directly due to cold exposure during recreation. It is possible that a higher proportion of cases occurring in rural areas is due to exposure during recreation compared to urban areas.…”
Section: Incidence and Mortality Of Accidental Hypothermiamentioning
confidence: 99%
“…[1][2][3][4] Mortality and the prevalence of hypothermia increases with the severity of injury and thus also with a higher injury severity score (ISS). 5 Lapostolle et al 6,7 found that the key risk factors of hypothermia were severity of injury, environmental conditions, and provided medical care.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] A pre-hospital, multicenter observational study from 2016 found that hypothermia (< 35°C) was present in 29 % of all trauma patients on arrival of emergency medical services (EMS). 7 Hypothermia develops in trauma patients for a number of reasons, including cold exposure at the scene of injury, during primary and secondary survey, administration of cold intravenous fluids and transfusion products, and heat loss from open body cavities due to injury or during surgery. Rapid detection and correction of hypothermia is therefore crucial in these patients, as the important coagulation processes to reduce blood loss are less effective with increasing degree of hypothermia.…”
mentioning
confidence: 99%